Nutritional Status in Multi Drug Resistance-Pulmonary Tuberculosis Patients - DR SURAJEET KUMAR PATRA,; DR ANJU JAIN,; DR B L SHERWAL,; DR ASHWANI KHANNA, (International Journal of Pharma and Bio Sciences, 2010)
Tuberculosis is a wasting disease. In the 21st century, tuberculosis is still the most frequent underlying cause of wasting worldwide. 100 subjects were enrolled in our study after informed consent. 50 study subjects were MDR-pulmonary tuberculosis patients and rest 50 were healthy controls. The nutritional status indices (Body Mass Index, Serum total protein, serum albumin, Blood hemoglobin) of study and control groups were compared. The p value of BMI and serum total protein between study and control group were found to be 0.01 and that of serum albumin and hemoglobin were found to be <0.0001. p value <0.05 is considered to be significant. The MDR-Pulmonary tuberculosis patients were having malnutrition and have lower level of serum protein, serum albumin and blood hemoglobin. Nutritional supplementation may help to improve outcome in tuberculosis patients. Nutritional supplementation may represent a novel approach for fast recovery in tuberculosis patients. In addition, raising nutritional status of population may prove to be an effective measure to control tuberculosis.